2011
DOI: 10.1177/1753193411422793
|View full text |Cite
|
Sign up to set email alerts
|

The effect of core suture flexor tendon repair techniques on gliding resistance during static cycle motion and load to failure: a human cadaver study

Abstract: The purpose of this study was to describe a modification of the Massachusetts General Hospital (MMGH) tendon repair and to compare it with three other suture techniques. Twenty human flexor digitorum profundus (FDP) tendons were randomly assigned to the modified Pennington (MP) suture and the MMGH suture. These were compared to the modified Kessler (MK) and Massachusetts General Hospital (MGH) sutures, using data from a previous study. All tendons were repaired with a similar epitendinous stitch and core sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…24, 30, 31 Moriya, et al showed no difference between work of flexion for 2- vs. 4-strand techniques. 31 Our repairs were performed with a looped suture employed in a locking Kessler configuration similar to Moriya’s modified Kessler. Using a looped suture in this fashion produces a repair with twice as many strands crossing the repair site, but achieved with the same number of needle passes (i.e., 4- and 8-strand techniques in our study had equivalent needle passes to 2- and 4-strand techniques in the published study).…”
Section: Discussionmentioning
confidence: 97%
“…24, 30, 31 Moriya, et al showed no difference between work of flexion for 2- vs. 4-strand techniques. 31 Our repairs were performed with a looped suture employed in a locking Kessler configuration similar to Moriya’s modified Kessler. Using a looped suture in this fashion produces a repair with twice as many strands crossing the repair site, but achieved with the same number of needle passes (i.e., 4- and 8-strand techniques in our study had equivalent needle passes to 2- and 4-strand techniques in the published study).…”
Section: Discussionmentioning
confidence: 97%
“…Increased tendon damage may increase adhesion formation. Multiple strands increase the bulk of the repair [1,7]. At the same time, more foreign material is presented on the tendon surface which can lead to increased external foreign body reaction.…”
Section: Discussionmentioning
confidence: 97%
“…Different suture techniques involving multiple suture strands and modern suture materials are used to improve the strength of the tendon repair to allow for active early motion of the injured digit [1][2][3][4][5][6]. Some studies have shown that an increased gliding resistance due to the suture material and suture technique cannot be overcome by passive mobilization alone, probably due to buckling up of the tendons inside the flexor sheath, or possibly as a result of post-injury oedema and exudative fluid reactions [7]. Active rehabilitation programs have been proven to minimize the formation of fibrous adhesions between the healing tendon and the tendon sheath [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study showed that all repairs failed by knot unraveling (Moriya et al, 2012). Therefore, the point of our study was to demonstrate that more throws are needed to prevent this problem.…”
Section: Referencesmentioning
confidence: 90%